Emotional intelligence, perceived stress and academic performance of Sri Lankan medical undergraduates - Mathangasinghe, Yasith; Ranasinghe, P.; Wathurapatha, W. S.; Ponnamperuma, G. (BioMed Central, 2017)
Background: Previous research has shown that higher Emotional Intelligence (EI) is associated with better academic and work performance. The present study intended to explore the relationship between EI, perceived stress and academic performance and associated factors among medical undergraduates. Methods: This descriptive cross-sectional research study was conducted among 471 medical undergraduates of 2nd, 4th and final years of University of Colombo, Sri Lanka. Students were rated on self administered Perceived Stress Scale (PSS) and Schutte Self-Report Emotional Intelligence Test (SEIT). Examination results were used as the dichotomous outcome variable in a logistic regression analysis. Results: Females had higher mean EI scores (p=0.014). A positive correlation was found between the EI score and the number of extracurricular activities (r=0.121,p=0.008). Those who were satisfied regarding their choice to study medicine, and who were planning to do postgraduate studies had significantly higher EI scores and lower PSS scores (p<0.001). Among final year undergraduates, those who passed the Clinical Sciences examination in the first attempt had a higher EI score (p<0.001) and a lower PSS score (p<0.05). Results of the binary logistic-regression analysis in the entire study population indicated that female gender (OR:1.98) and being satisfied regarding their choice of the medical undergraduate programme (OR:3.69) were significantly associated with passing the examinations. However, PSS Score and engagement in extracurricular activities were not associated with ‘Examination Results’. Conclusions: Higher EI was associated with better academic performance amongst final year medical students. In addition a higher EI was observed in those who had a higher level of self satisfaction. Self-perceived stress was lower in those with a higher EI. Enhancing EI might help to improve academic performance among final year medical student and also help to reduce the stress levels and cultivate better coping during professional life in the future.
Keywords: Emotional intelligence, Perceived stress, Academic performance, Medical students, Sri Lanka